The Future of Inclusive Education: Preparing Students with Special Needs for the World of Work - A. Erni Ratna Dewi; Sitti Nurfaidah (Journal of Pedagogi, 2024)
Inclusive education is an important issue in ensuring equal access to education for individuals with special needs around the world. Despite its implementation in various countries, challenges such as skills gaps, lack of assistive technology, and social stigma still hinder the integration of students with special needs into the workforce. This research aims to explore these issues and find solutions that can support the development of inclusive education that is more oriented towards the needs of the world of work. Using a descriptive qualitative approach, the research involved various stakeholders, including students, teachers, parents, employers and policymakers, to identify challenges and opportunities for collaboration between inclusive education and industry. The results showed the need for curriculum revision, integration of assistive technology and increased collaboration between inclusive schools and the world of work to address the skills gap. In addition, strong regulatory support and adequate investment from the government as well as the private sector are necessary to create an inclusive and equitable work environment for students with special needs